A gestão pedagógica escolar e a interconexão com outros contextos educativos - Colussi, Daiane (2023)
This dissertation is linked to Research Line 2 (LP2), Pedagogical Management and Educational Contexts, of the Graduate Program in Public Policies and Educational Management, at the Federal University of Santa Maria (UFSM). The interest in studying the theme “School pedagogical management and the interconnection with other educational contexts”, arose from the concern to re-signify the PROFESP Project (Programa Forças no Esporte) financed by the Federal Government and applied by the Air Base of Santa Maria in partnership with the municipality at the school where I work in the 5th grade of elementary school, Escola Municipal de Ensino Fundamental Padre Gabriel Bolzan. As a concern, the following research problem arose: How does school pedagogical management connect with other educational contexts, impacting the quality of the learning process? For this, the following general objective was organized: resignify the possibilities, challenges and limitations of school pedagogical management with students who live/experience other educational contexts. As specific objectives: re-signify pedagogical management and other educational contexts; reflect on life histories of subjects from other educational/cultural contexts providing local and global socio-cultural activities; present a possible implementation proposal for future partnerships between school institutions and other educational contexts. The methodology is anchored in a qualitative, ethnographic, autobiographical, applied and implied research, and can also be characterized as a case study. The purposes of the studies, the author's pedagogical practice, interconnected to other educational contexts and the students' school life with the insertion of the PROFESP project in the school were analyzed. The educational product developed was an educational folder, demonstrating how considerable this activity is with other educational contexts, strengthening and expanding the PROFESP project in other educational institutions. The practices, knowledge, experiences and experiences go beyond the guidance/learning presented by teachers. As a conclusion, significant moments were obtained for all participating subjects, it was a professional and personal growth, articulating theory and practice in different educational contexts. The interconnections with other educational contexts made possible the knowledge of different identities, cultures, dreams and hopes. One of the innovations of this research was to interconnect different local/global educational contexts, with a view to an integral, citizen, ethical, multicultural, planetary and peaceful education.